MOTIVATION OF COMMUNITY MEMBERS TO JOIN INDORUNNERS SURABAYA - Andry Pratama Halim (CALYPTRA, 2018)
Excercise community has been a trend in recent years and because one of many ways for people to fulfill their need to excercise . One of the excercise communities in Indonesia is IndoRunners. This Research intends to find answers behind the phenomenon that people joined the community contrary to be fact that vit requires more effort. This research intends to study the phenomenon and will try to reveal motivation of members behind joining IndoRunners Surabaya. Using Victor Vroom's Expectancy theory, the motivation is divided into expectancy, instrumentality, and valence. The researcher expects to find insight through these elements to find answer and create better understanding to the phenomenon. the result show that expectations of members to join IndoRunners Surabaya which developed the effent in realizing those expectations, and is supported by the reward that they perceived. Knowledge from this research may benefit excercise communities or organizations in sports and excercise industrics.